ЛЕЧЕНИЕ БОЛЬНЫХ АРТЕРИАЛЬНОЙ ГИПЕРТОНИЕЙПРЕПАРАТОМ ФОЗИКАРД В АМБУЛАТОРНЫХ УСЛОВИЯХ («Наука и здравоохранение», 2026)
ЛЕЧЕНИЕ БОЛЬНЫХ АРТЕРИАЛЬНОЙ ГИПЕРТОНИЕЙПРЕПАРАТОМ ФОЗИКАРД В АМБУЛАТОРНЫХ УСЛОВИЯХ